Begonia fuyangii, a new species of Begonia sect. Coelocentrum (Begoniaceae) from Guangxi, China - Xi, Hou-Cheng; Zhou, Jin-Ye; Nong, Fu-Yang; Li, Ren-Kun; Shen, Jian-Yong; Tian, Dai-Ke; Wang, Wen-Guang (Phytotaxa, 2025)
Begonia fuyangii (sect. Coelocentrum), a new species from Guangxi of China, is described and illustrated. It resembles B. yizhouensis but can be distinguished by its leaf blade color, maculation and indumentum, smaller staminate flower, ovary 3-loculed and placentation axile. It also resembles B. jingxiensis but can be distinguished by its stipule shape, leaf blade color, maculation and margin, shape of bracts, and number of staminate and pistillate flower tepals.